2019
DOI: 10.1002/celc.201900668
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Ruthenium Oxide‐Based Composites for Supercapacitor Applications

Abstract: Electrochemical energy storage has emerged as one of the principal topics of present‐day research to deal with the high energy demands of modern society. Accordingly, besides fuel cells and battery technologies, interesting and challenging results have been observed in the recent past, during the materialization of “supercapacitors” or “ultracapacitors”, which have provoked a sharp increase in research inclination to revisit this aspect of renewable and sustainable energy storage. Supercapacitor performances a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
147
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(155 citation statements)
references
References 300 publications
(392 reference statements)
2
147
0
Order By: Relevance
“…This performance is significantly higher than just that of CNF electrodes, and the ability to deliver higher specific power at higher specific energy is enhanced when compared to many carbon and metal oxide based electrodes. [77][78][79] The present specific energy results are comparable to other high specific capacitance yielding electrodes, such as RuO 2 -CNT/CNF-based electrodes, 50,63,64,72 RuO 2 -graphene oxide-based electrodes 54,73 and other RuO 2composite based electrodes. 49,74…”
Section: Materials Advancessupporting
confidence: 75%
“…This performance is significantly higher than just that of CNF electrodes, and the ability to deliver higher specific power at higher specific energy is enhanced when compared to many carbon and metal oxide based electrodes. [77][78][79] The present specific energy results are comparable to other high specific capacitance yielding electrodes, such as RuO 2 -CNT/CNF-based electrodes, 50,63,64,72 RuO 2 -graphene oxide-based electrodes 54,73 and other RuO 2composite based electrodes. 49,74…”
Section: Materials Advancessupporting
confidence: 75%
“…Comparison of the gravimetric capacitance of supercapacitor electrode materials. The data for gravimetric capacitance of supercapacitor materials with some selected nanostructures are taken from the corresponding articles: pristine carbon, [13] MnO 2 -based materials, [22] Fe-based materials, [18,23] RuO 2 -based structure, [15] VN structure, [24] 2D materials, [16,21] and conducting polymers. [13] Specific capacitance of doped nanocarbon is taken from the references cited in this article and also presented are the electrode performances in details in Table 1 (AC: activated carbon; MWCNT: multiwalled carbon nanotube; CDC: carbide derived carbons; rGO: reduced graphene oxide; HPC: hierarchical porous carbon; BP: black phosphorene; RP: red phosphorene; PANI: polyaniline; PPy: polypyrrole; PTh: polythiophene; PMT: poly(3-methylthiophene); PEDOT: poly(3,4-ethylenedioxythiophene); PEPT: poly(4-flourophenyl-3-thiophene)), VN: vanadium nitride.…”
Section: Scope Of the Reviewmentioning
confidence: 99%
“…[234] The underlying observation is that unstable carboxyl groups are neutralized and reduced during charge-discharge while the electrodes are subjected to KOH medium. [227] It has also been reported that the acidic sites (carboxyl, phenol) on nanocarbon surface play a dominant role and react with OH − ions in alkaline medium (Equations (15) and (16)) while the basic sites are unfavorable for the redox reactions [49,227] On the other hand, O-functionalized nanocarbons show better supercapacitive performance in H 2 SO 4 medium due to the higher ionic mobility and better accessibility of the surface by smaller ions. [216] Meanwhile, the basic functional groups (carbonyl and quinone) present on the nanocarbons react with protons contributing pseudocapacitance in acidic aqueous electrolyte.…”
Section: Effect Of Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…Ruthenium oxide showed the best performance among all tested TMOs so far due to its highly reversible redox reactions, good thermal stability, wide potential window, metallic-type conductivity, and long cycle life. [16] However, the practical use of RuO 2 -based electrodes is limited by the high cost and low abundance. Therefore, many studies were directed to explore low-cost alternatives to RuO 2 such as Ni 2 O 3 , NiO, V 2 O 5 , Fe 3 O 4 , MnO 2 , MnO, MoO 3 , black TiO 2 , and their composites.…”
Section: Introductionmentioning
confidence: 99%